Contrasted hydrological responses to forest harvesting in two large neighbouring watersheds in snow hydrology dominant environment: implications for forest management and future forest hydrology studies. Issue 26 (2nd December 2013) - Zhang, Mingfang; Wei, Xiaohua
Abstract Two large neighbouring watersheds, the Bowron (3420 km2) and Willow (2860 km2) situated in the central interior of British Columbia, Canada, were used to compare their hydrological responses to forest harvesting in snow‐dominant environment. Both watersheds had experienced significant, comparative forest harvesting level. The long‐term hydrometric and timber harvesting data (>50 years of records) were analysed using time series analysis to examine the hydrological impacts of forest harvesting. The hydrological variables including mean, peak and low flows over annual and seasonal scales (spring snowmelt, summer rain and winter base flow) were tested separately. Results showed that forest harvesting in the Willow watershed significantly increased annual and spring mean flows as well as annual and spring peak flows, whereas it caused an insignificant change on those hydrological variables in the Bowron watershed. The contrasted differences in hydrological responses are due to the differences in topography, spatial heterogeneity, forest harvesting characteristics and climate between two watersheds. The relative uniform topography and climate in the Willow watershed may promote hydrological synchronization effects, whereas larger variation in elevations, together with forest harvesting that occurred at lower elevations, may cause hydrological de‐synchronization effect in the Bowron watershed. The contrasted results demonstrate that the effects of forest harvesting on hydrology in large watersheds are likely watershed specific, and any attempt to generalize hydrological responses to forest harvesting must be carried out with caution. A landscape ecological perspective is critically needed for future forest hydrology studies, particularly for large watersheds. Copyright © 2013 John Wiley & Sons, Ltd.